Association of ABO Blood Groups with Craniofacial Morphology among Orthodontic Patients in Selected Private Clinics of Kathmandu - Gupta, Sanjay P (Journal of Institute of Medicine Nepal, 2019)
Introduction The craniofacial morphology and blood groups both are related to genetic components, hence it can be hypothesized that blood groups have an association with craniofacial morphology. Some studies showed the relationship whereas others could not find any relationship in different population. The aim of this study was to find out the relationship between ABO blood groups and craniofacial morphology among orthodontic patients of Kathmandu district. Methods In this cross sectional analytical study, 385 participants (age range from 13-45 years) were selected among the orthodontic patients who came for orthodontic treatment in private orthodontic clinics. After obtaining written consent, all the patient’s demographic information were recorded and lateral cephalograms were obtained from the patient’s record. Blood group of all the participants was recorded. Results Among 385 participants, 162 (42.07%) were male while 223 (57.93%) were female and the mean age was 16.31±4.38 years. Twenty cephalometric parameters depicting craniofacial morphology were digitally analyzed using lateral cephalograms. The prevalence of blood group O patients was highest (32.20%) followed by blood group B (30.64%), blood group A (29.88%) and blood group AB (7.28%). Statistical analysis with ANOVA revealed nine out of twenty cephalometric parameters were statistically significant among different blood groups (p<0.05). Tukey post hoc test was done to find out the difference among the groups. Conclusion The evaluation of relationship between blood group and craniofacial morphology revealed that blood groups have association with some craniofacial parameters. This suggests, there may be some genetic influence of ABO blood group on craniofacial morphology.